IMPACT OF THE EXERCISE PROGRAMME BASED ON FLOWIN CONCEPT AND IMPLEMENTED IN PHYSICAL AND SPORTS EDUCATION CLASSES ON FUNCTIONS OF THE POSTURAL MUSCLE SYSTEM - Elena Bendíková; Ratko Pavlović (Sport Scientific And Practical Aspects, 2025)
This article presents the partial task and its aim, focused on the targeted workout programme consisting of Flowin exercises. The workout programme was implemented among the pupils of the 8 th class in physical and sports education classes and it should develop into the basis for innovations in this school subject. We recorded the significant changes at 5% level among both the girls and the boys. Initial and also final measurements revealed that the both experimental groups most frequently suffered from shortening of the knee flexors. The girls reached better changes in functions of postural muscles. However, the boys had bigger differences between averages of initial and final measurements. Furthermore, we would like to point out the benefits of the exercise programme within physical and sports education. This programme has a positive impact on functionality of the postural muscle system, and at the same time, it prevents improper body posture. What is more, such a programme could increase motivation and arouse interest in sports activities among teenagers. Experimental verification of the “intensification factor” in physical and sports education classes at elementary schools means the knowledge and a starting point for theory and practice of the physical and sports education. The article is the part of the project called: ,,The article is a part of the grant research task VEGA No. 1/0757/12 titled Reactive and Adaptation Indicators of Changes in Physical and Mental Abilities of Sportsmen in Connection to Biorhythms with Periods of Different Lengths.“